Update on medical treatment of small intestinal neuroendocrine tumors. Issue 9 (1st September 2016) - Pusceddu, Sara; Femia, Daniela; Lo Russo, Giuseppe; Ortolani, Silvia; Milione, Massimo; Maccauro, Marco; Vernieri, Claudio; Prinzi, Natalie; Concas, Laura; Leuzzi, Livia; De Braud, Filippo; Buzzoni, Roberto
ABSTRACT: Introduction : Small intestinal (SI) neuroendocrine tumors (NETs) are relatively rare tumors. Due to the lack of symptom or specific symptoms, SI-NETs are often diagnosed at an advanced stage, making therapy challenging. The management of patients with advanced stage SI-NETS requires a multidisciplinary approach that combines surgical and medical treatment including novel targeted molecular therapies. Areas covered : This article summarizes current strategies for the medical treatment of SI-NETS. Expert commentary : The treatment plan of advanced-stage SI-NETs should be tailored in a case-by-case manner with the adoption of a multidisciplinary approach that combines different treatment options, including biological targeted therapies. In particular, we believe that the identification of the optimal treatment sequence(s), correct treatment timing and the selection of patients eligible to different treatments need specific investigation in controlled clinical trials.